Peran Tata Usaha dalam Pelayanan Administrasi Kesiswaan di SMP Negeri 6 Prabumulih - Prima Sena Ardinata; Ade Akhmad Saputra; Rabial Kanada (NAAFI: JURNAL ILMIAH MAHASISWA, 2026)
This study aims to examine the role of the administrative office in student affairs administration at SMP Negeri 6 Prabumulih. The administrative office plays a crucial role in ensuring the smooth operation of school administration, particularly in data management and services provided to students. This study employs a qualitative approach using a descriptive method. Data collection techniques included observation, interviews, and documentation. The research informants consisted of the administrative staff. The results indicate that the administrative office plays a role in managing student data, archiving student documents, preparing correspondence, managing attendance, and providing administrative services related to student needs. Additionally, the administrative office serves as a facilitator for smooth communication between the school, students, and parents. Student administrative services at the school have been functioning fairly well, although some challenges remain, such as limited supporting facilities and a backlog of administrative work. Therefore, improvements in facilities and more effective work management are needed to ensure that student administrative services can operate optimally